Pengaruh Kebiasaan Mengemukakan Pendapat Teknik Debat Terhadap Perilaku Asertif - Annisa Arrumaysa Daulay (Program Studi Bimbingan Penyuluhan Islam Fakultas Dakwah dan Komunikasi, 2019)
This study aims to determine the effect of the habit of expressing the debate technique on student assertive behavior. This type of research is experimental research with a pre-test and post-test group design. The subjects of this study were students of class X-10 Man 2 Model Medan, amounting to 18 students who had low assertive behavior determined from the results of the pre-test questionnaire. The instrument used was a questionnaire to collect data about assertive behavior that had previously been tested to determine the validity and reliability of the questionnaire. The data analysis technique uses a different test (t-test). The results showed that there was an influence of the habit of expressing opinions on students' assertive behavior.